2015
DOI: 10.2147/rmhp.s70173
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to health care for undocumented immigrants: a literature review

Abstract: With the unprecedented international migration seen in recent years, policies that limit health care access have become prevalent. Barriers to health care for undocumented immigrants go beyond policy and range from financial limitations, to discrimination and fear of deportation. This paper is aimed at reviewing the literature on barriers to health care for undocumented immigrants and identifying strategies that have or could be used to address these barriers. To address study questions, we conducted a literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
334
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(361 citation statements)
references
References 66 publications
14
334
1
12
Order By: Relevance
“…The two-day ECM hosted by University of Crete, was attended by sixty-nine (69) international, regional, and local experts, across disciplines, and with a focus on refugee and migrant care from fourteen (14) countries. Participants were chosen on the basis of their experience and knowledge in the field of primary care and/or care for refugees.…”
Section: Focussing On Compassionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-day ECM hosted by University of Crete, was attended by sixty-nine (69) international, regional, and local experts, across disciplines, and with a focus on refugee and migrant care from fourteen (14) countries. Participants were chosen on the basis of their experience and knowledge in the field of primary care and/or care for refugees.…”
Section: Focussing On Compassionmentioning
confidence: 99%
“…The literature search and interviews with experts found that in order to provide compassionate care crucial problems and barriers occur at the levels of professional, patient, and organisation. Many studies identified the training of professionals in culturally sensitive aspects of care as a core enabler or a critical element of improvement interventions [6,[12][13][14][15].…”
Section: Highlights From the Ecm: The Need For Compassionate Carementioning
confidence: 99%
“…4 Yet, fear of deportation has been documented as a serious barrier in 65% of research studies on access to healthcare by undocumented migrants. 5 The risk of deterring people from seeking treatment has now been recognised by the prime minister in the wake of the Grenfell Tower tragedy; she told the House of Commons that "I would also like to reassure people that we will not use this tragic incident as a reason to carry out immigration checks [and] will make sure that all victims, irrespective of their immigration status, will be able to access the services they need, including healthcare and accommodation." 6 Reassurances of this kind, however, are no substitute for a legal guarantee of the human right to health, which the UK has signed up to in international law.…”
mentioning
confidence: 99%
“…Recent increased migration rates around much of the world resulted in immigration policies by numerous governments to inhibit migration, including limiting access to health care for immigrants [e.g., Canada, Costa Rica, several European countries, the United States (US), and Scandinavia; Hacker, Anies, Folb, & Zallman, 2015]. Insufficient health care can put migrants at great risk.…”
mentioning
confidence: 99%
“…Moreover, 39% of foreign-born, non-citizen Latinos and almost half of undocumented Latinos lack insurance due in part to ineligibility for the ACA and other government assistance (Krogstad & Lopez, 2014). Thus, Latina immigrants often lack a regular health care provider during their initial months in the US due to inability to afford care, as well as barriers such as (b) unfamiliarity with the US health care system, (c) preference for alternative forms of treatment, (d) difficulties due to language and cultural differences, (e) discrimination, and/or (f) unauthorized immigration status and fear of deportation (De Jesus & Miller, 2015; Escarce & Kapur, 2006; Gurman & Becker, 2008; Hacker, et al, 2015; Marshall, Urrutia-Rojas, Mas, & Coggin, 2005). These obstacles are especially problematic for Latina young adults in the US given that medical practitioners recommend that Latina young women receive regular cancer screening due to the disproportionately high prevalence rates in the US (Bickell, 2002; Nodora et al, 2015; Zhan & Lin, 2014).…”
mentioning
confidence: 99%